Prevalence of side-effects and change in nutritional status during radical radiotherapy for head and neck malignancies at Tygerberg Academic Hospital, Western Cape, South Africa - De Pomeroy-Legg, Jeanita (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--Stellenbosch University, 2008.